Catch Efficiency of Monofilament Gill Nets Configured at Various Colors and Hanging Ratios - Orsay, Bulent; Dartay, Murside (Medwell Online, 2011)
This study has been carried out between September 2004 and April 2006 at 8 different stations located within the fishing zone of the Keban Dam Lake Cemisgezek Fishery Cooperative (Elazig/Turkey). In order to identify the effect of colored gill nets in fish catching in. the Keban Dam lake, nets of 40 mm mesh size were colored green, blue, burgundy and black and these 4 different colored, same mesh size nets were equipped with 0.50 and 0.67 hanging ratios, totaling up to 8 nets of different configurations. During the 2 years research, a total of 1169 fish were caught, 606 of which were caught in. the monofilament gill nets with 0.50 hanging ratio and the remaining 563 caught in the monofilament gill nets with 0.67 hanging ratio. The fish caught in the nets were classified according to the hanging ratio, mesh size and the color of the nets. Then the total sizes of the fish were measured and they were weighed; lastly, the mean fish length and weight as well as the standard deviation from these mean values were calculated and recorded. The statistical relation between the fish populations caught with nets possessing differing mesh size, color and hanging ratio properties were compared using the chi(2)-test. The material color of the gill nets was found to be effective on the catch efficiency. Barbus rajanorum mystaceus and Capoeta trutta (Cyprinidae)were caught in black and green nets with 0.40 mm mesh size and 0.50 hanging ratio while mostly B. esocinus and B. xanthopterus (Cyprinidae) were caught in the blue nets with the same mesh size and 0.67 hanging ratio. In conclusion, it is determined that black gill nets can be used for Capoeta trutta, burgundy for carp, green for Barbus rajanorum mystaceus and blue for barbell in Keban Darn lake in Cemisgezek district.
Keywords: Keban dam lake; colored gill nets; hanging ratio; black gill nets; Turkey